0835 Substance Abuse, An Important Factor in the Evaluation of Hypersomnia Disorders. (25th May 2022) - Patel, Kevin; Schwartz, Daniel; Anderson, William; Andrews, Arthur; Elballat, Mohammad
Abstract: Introduction: A detailed history is essential in the diagnostic workup of hypersomnia, but can be limited by withheld information. A common piece of information hidden during a detailed history is the presence of substance abuse/use. AASM guidelines dictate an MSLT study must be conducted in patients free from certain psychoactive medications. The guidelines mention these therapies be stopped at least 2 weeks prior to the planned study date and recommend utilizing an urinary drug screen to evaluate patients who undergo the study. From review of the available literature, substance abuse has significant effects upon sleep architecture and the development of hypersomnia. Certain substances such as stimulants may normalize a disorder of hypersomnolence and the opposite holds true for sedatives and depressants. Report of Cases: Mr. RB, a 52-year-old Veteran with a medical history inclusive of hypertension, DM2, cocaine abuse and hypersomnia. Initial workup demonstrated presence of OSA (AHI 16.4, O2 nadir 87%). After diagnosing and treating OSA, Mr. RB returned to clinic with complaints of persistent hypersomnia. Mr. RB was then evaluated by MSLT study for further assessment. Patient reported absence of cocaine use at time of clinic visit and prior to study. The results of the MSLT demonstrate MSL of 0.5 minutes and 3/4 SOREMs. Unfortunately, UDS verified Mr. RB had recently used cocaine (581 ng/mL). Mr. RB was then followed up in clinic due to persistent symptoms, with new reports of cataplexy, hypnopompic hallucination and sleep paralysis. Mr. RB also reported abstaining from cocaine use. A repeat MSLT was performed with MSL of 1.2 minutes and 3/5 SOREMS. Unfortunately, Mr. RB was again found to have recently used cocaine (441 ng/mL) on UDS. Mr. RB was then lost to follow-up. Conclusion: This case demonstrates the importance of obtaining a truthful history during the evaluation of a sleep disorder. This case also demonstrates the utility of verifying the history obtained with laboratory testing. During this case, the physicians working with Mr. RB demonstrated detailed note documentation regarding reports of cocaine abstinence which was later disproven during the drug screening during the sleep study and follow up clinic appointment. Support (If Any): 1. Angarita, G. A., Emadi, N., Hodges, S., & Morgan, P. T. (2016). Sleep abnormalities associated with alcohol, cannabis, cocaine, and opiate use: A comprehensive review. Addiction Science & Clinical Practice, 11(1). https://doi.org/10.1186/s13722-016-0056-72 . Anniss, A. M., Young, A., & O'Driscoll, D. M. (2016). Importance of urinary drug screening in the multiple sleep latency test and maintenance of wakefulness test. Journal of Clinical Sleep Medicine, 12(12), 1633–1640. https://doi.org/10.5664/jcsm.63483 . Dzodzomenyo, S., Stolfi, A., Splaingard, D., Earley, E., Onadeko, O., & Splaingard, M. (2015). Urine toxicology screen in multiple sleep latency test: The correlation of positive tetrahydrocannabinol, drug negative patients, and narcolepsy. Journal of Clinical Sleep Medicine, 11(02), 93–99. https://doi.org/10.5664/jcsm.44484 . Krahn, L. E., Arand, D. L., Avidan, A. Y., Davila, D. G., DeBassio, W. A., Ruoff, C. M., & Harrod, C. G. (2021). Recommended protocols for the multiple sleep latency test and maintenance of wakefulness test in adults: Guidance from the American Academy of Sleep Medicine. Journal of Clinical Sleep Medicine, 17(12), 2489–2498. https://doi.org/10.5664/jcsm.96205 .Roehrs, T. A., & Roth, T. (2015). Sleep disturbance in substance use disorders. Psychiatric Clinics of North America, 38(4), 793–803. https://doi.org/10.1016/j.psc.2015.07.0086 . emasinghe Bandaralage, S., Sriram, B., Rafla, M., Sharma, N., & McWhae, S. (2021). P130 an audit of urinary drug screening use in multiple sleep latency and maintenance of wakefulness testing in an australian tertiary centre. SLEEP Advances, 2(Supplement_1). https://doi.org/10.1093/sleepadvances/zpab014.171